Adaptation and Validation of the Indonesian Version of Behavioral Activation for Depression Scale – Short Form (BADS-SF) Using Confirmatory Factor Analysis and Rasch Modeling - Salma, Salma; Handoyo, Restu Tri; Puspitasari, Ajeng J.; Hidayat, Rahmat; Leonard, Rachel; Kanter, Jonathan (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2026)
The Behavioral Activation for Depression Scale – Short Form (BADS-SF) is a brief instrument designed to measure activation levels in individuals undergoing behavioral activation (BA) therapy for depression. With the broad potential for implementing BA therapy, including in Indonesia, the BADS-SF needs to be cross-culturally adapted. While the original validation study supported a two-factor model, subsequent adaptations, particularly in non-Western settings, have yielded inconsistent results. In addition, given the practical application of the BADS-SF total score as an overall indicator of behavioral activation, it is essential to evaluate its psychometric properties as a unidimensional measure. The objectives of this study are: (1) to culturally adapt the BADS-SF into the Indonesian language (Bahasa Indonesia); (2) to examine its underlying factor structure and convergent validity; and (3) to evaluate its psychometric properties using item response theory (IRT), specifically Rasch modeling. The cultural adaptation process demonstrated good content validity based on Aiken’s V (.75 to 1 for all items) and confirmed the scale readability. The confrmatory factor analysis (CFA) results revealed a different factor structure than the original, with a 6-item one-factor model providing the best fit and confirmed convergent validity. Rasch analysis further showed that the Indonesian version of BADS-SF had good psychometric properties, including excellent item reliability, acceptable person reliability, and supported unidimensionality following the exclusion of a misfitting item (Item 8). Based on the overall results, the 6-item version of BADS-SF Bahasa Indonesia is recommended to be used for both research and clinical practice. Further implications of the findings are discussed.